Mechanisms of nuclear lamina growth in interphase - Zhironkina, Oxana A; Kurchashova, Svetlana Yu; Pozharskaia, Vasilisa A; Cherepanynets, Varvara D; Strelkova, Olga S; Hozak, Pavel; Kireev, Igor I (Histochemistry and cell biology, 2016)
The nuclear lamina represents a multifunctional platform involved in such diverse yet interconnected processes as spatial organization of the genome, maintenance of mechanical stability of the nucleus, regulation of transcription and replication. Most of lamina activities are exerted through tethering of lamina-associated chromatin domains (LADs) to the nuclear periphery. Yet, the lamina is a dynamic structure demonstrating considerable expansion during the cell cycle to accommodate increased number of LADs formed during DNA replication. We analyzed dynamics of nuclear growth during interphase and changes in lamina structure as a function of cell cycle progression. The nuclear lamina demonstrates steady growth from G1 till G2, while quantitative analysis of lamina meshwork by super-resolution microscopy revealed that microdomain organization of the lamina is maintained, with lamin A and lamin B microdomain periodicity and interdomain gap sizes unchanged. FRAP analysis, in contrast, demonstrated differences in lamin A and B1 exchange rates; the latter showing higher recovery rate in S-phase cells. In order to further analyze the mechanism of lamina growth in interphase, we generated a lamina-free nuclear envelope in living interphase cells by reversible hypotonic shock. The nuclear envelope in nuclear buds formed after such a treatment initially lacked lamins, and analysis of lamina formation revealed striking difference in lamin A and B1 assembly: lamin A reassembled within 30 min post-treatment, whereas lamin B1 did not incorporate into the newly formed lamina at all. We suggest that in somatic cells lamin B1 meshwork growth is coordinated with replication of LADs, and lamin A meshwork assembly seems to be chromatin-independent process.
Keywords: Animals; Nuclear Lamina; jaderná lamina; Cell cycle; lidé; Mice; prasata; interfáze; kultivované buňky; myši; Cricetulus; Interphase; Nucleus; Cells, Cultured; DNA replication; Swine; zvířata; Microdomains; Nuclear lamina; Humans